Early intervention in eating disorders: introducing the chronopathogram - Antonio Preti; Francesco Bevione; Maria Carla Lacidogna; Andrea Raballo; Michele Poletti; Giovanni Abbate-Daga (Eating and Weight Disorders)
Abstract Eating disorders (EDs) pose significant challenges to mental and physical health, particularly among adolescents and young adults, with the COVID-19 pandemic exacerbating risk factors. Despite advancements in psychosocial and pharmacological treatments, improvements remain limited. Early intervention in EDs, inspired by the model developed for psychosis, emphasizes the importance of timely identification and treatment initiation to improve prognosis. Challenges in identifying prodromal phases and measuring the duration of untreated illness highlight the complexity of early intervention efforts in EDs. Current research focuses on reducing the duration of untreated eating disorder (DUED) and understanding the cognitive and behavioral symptoms preceding ED onset. However, current early intervention programs for EDs showed mixed results, necessitating further investigation. We introduce here the chronopathogram, a tool that may aid in precisely investigating the role of development in EDs. A chronopathogram is a graphical representation of pathological events as they unfold over time. Understanding the neurodevelopmental aspects of EDs and utilizing tools like the chronopathogram can aid in tracking the unfolding of symptoms over time, facilitating early detection and intervention efforts. Overall, addressing the key factors influencing the onset and course of EDs is essential for effective early intervention in these conditions. Level of evidence: Level V narrative review.